Penatua Generasi Milenial dalam Pendidikan dan Keagamaan: (Studi Kasus pada Penatua GMIM di Wilatah Tomohon 3) - Aljuanika Ering; Mercy Waney (Institut Agama Kristen Negeri Manado, 2021)
ABSTRACT. This study aims to describe how the education and religion of the millennial generation elders in the Tomohon 3 region, describe what causes the election of the millennial generation elders in the Tomohon 3 region with regard to their education and religion. The data in this study were observed and collected through interviews with elders and millennial generation members, after which they were analyzed. It was found that the education of the elders of the millennial generation in the Tomohon 3 region was stratum 1 and stratum 2 and their religion was accustomed to being active in both worship, seminar and leadership training activities within the church. The election of millennial generation elders is due to the idea that when they have good education and religion, they can carry out their duties as elders well too. For this reason, elders can carry out their responsibilities properly with the support of existing members.